Microbicides 2006 conference. - Ramjee,G; Shattock,R; Delany,S; McGowan,I; Morar,N; Gottemoeller,M (AIDS Res Ther, 2006)
Current HIV/AIDS statistics show that women account for almost 60% of HIV infections in Sub-Saharan Africa. HIV prevention tools such as male and female condoms, abstinence and monogamy are not always feasible options for women due to various socio-economic and cultural factors. Microbicides are products designed to be inserted in the vagina or rectum prior to sex to prevent HIV acquisition. The biannual Microbicides conference took place in Cape Town, South Africa from 23-26 April 2006. The conference was held for the first time on the African continent, the region worst affected by the HIV/AIDS pandemic. The conference brought together a record number of 1,300 scientists, researchers, policy makers, healthcare workers, communities and advocates. The conference provided an opportunity for an update on microbicide research and development as well as discussions around key issues such as ethics, acceptability, access and community involvement. This report discusses the current status of microbicide research and development, encompassing basic and clinical science, social and behavioural science, and community mobilisation and advocacy activities.